Natural environmental conditions and collaborative efforts provide the secret to success for sand tiger shark Carcharias taurus reproduction in aquaria. Issue 5 (5th August 2020) - Wyffels, Jennifer; Coco, Chris; Schreiber, Chris; Palmer, Daniel; Clauss, Tonya; Bulman, Frank; George, Robert; Pelton, Craig; Feldheim, Kevin; Handsel, Tim
Abstract: Sand tiger sharks are an iconic large shark species held in aquaria worldwide. They rarely reproduce under managed care, with only seven aquaria reporting limited and sporadic success. For the first time in the Americas, a full‐term young was born in an aquarium. The young was the result of breeding among a group of sharks purposefully brought together in 2016 for reproduction. Sharks were maintained in natural seawater and exposed to natural light and seasonal temperature fluctuations similar to their in situ counterparts. Decreased food consumption associated with breeding season and gestation was observed. Gestation time estimated from breeding observations and parturition was 321 days. Although the neonate was stillborn, this was a significant achievement. The husbandry details described within will be useful for other aquaria striving to support the reproduction of sand tiger sharks. Abstract : Mature sand tiger sharks from aquaria in Pennsylvania, South Carolina and Tennessee were relocated to Florida for reproduction. The group was maintained in natural seawater and exposed to natural light and seasonal temperature fluctuations similar to their in situ counterparts. After 2 years together, for the first time in the Americas, a pair of sand tiger sharks produced a full‐term young. Research Highlights: For the first time in the Americas, a pair of sand tigers produced a full‐term young. Maintaining sand tiger sharks in aquaria with husbandry conditions similar to their natural environment supports reproduction.